(untitled) (Psychology Travelogs, 2024)
The article is devoted to the search for ways of post-covid rehabilitation of the teacher of the network of open distance education. The study was carried out with the grant support of the National Research Fund of Ukraine within the framework of the project «Post-traumatic social and psychological rehabilitation of participants in the educational process in the activities of psychological service workers». It is revealed that distance learning is a certain form of organization of the educational process in a specially created educational environment using modern information and communication technologies. The article presents the results of the research, in particular, the psychological features of a safe educational environment, as well as an analysis of the state of the environment of educational institutions in the conditions of post-covid rehabilitation. The author also draws attention to the fact that in the post-war period, 1,202 teachers sought psychological help, while 694 teachers did not. Among the education seekers, 1,151 people applied for psychological help. The article found out that the factors of successful psychological adaptation can be considered internal and external resources, especially resources of stress resistance, vitality, adaptive coping strategies, resilience, post-traumatic growth. It has been proven that the main stages of post-covid rehabilitation in working with teachers are disorder, stability and growth. The article determines that understanding internal supports, meditation, control of sensory stimuli, «inform-detox», transformation of potential into positive things, talking about what worries and disturbs, contribute to the improvement of the psycho-emotional state and increase of self-regulation. The article will be useful to practical psychologists and teachers of distance education.